Exploring the behaviour of the twist-bend nematic phase using NMR with a variety of spin probes. Issue 13 (20th October 2020) - Ferrarini, Alberta; Greco, Cristina; Luckhurst, Geoffrey R.; Timimi, Bakir A.; Zimmermann, Herbert
ABSTRACT: Here we discuss the use of deuteriated probe molecules in NMR studies of the nematic (N) and twist-bend nematic (NTB ) phases formed by the generic liquid crystal dimer CB7CB. The key properties of three probes dissolved in the NTB phase investigated are the orientational order Szz B and the conical angle, θ0, of the director with respect to the spectrometer field. In addition for one probe 5CB-d2 it is possible to obtain a measure of the phase chirality from the difference in the quadrupolar splittings given by the prochiral pair of deuterons. The relative simplicity of the probes facilitates the determination of the key properties which are obtained using two different approaches. GRAPHICAL ABSTRACT: uf0001